Transformation of social‐ecological systems in the Songhua River Basin, Northeast China: Lessons for a more sustainable development - Na Sa; Jinyu Zhao; Xuyang Kou; Shuanning Zheng; Zhaohua Lu; Jan Christoph Axmacher; Weiguo Sang (People and Nature, 2025)
Abstract Social‐ecological systems (SES) are coupled systems formed by the intricate interactions between humans and nature. Our movement towards sustainable lifestyles requires a robust understanding of these interactions. Achieving a sustainable win‐win situation for both social and ecological systems, therefore, necessitates a sound scientific framework outlining the direct and indirect interdependence between a region's inhabitants and the changing natural environment they live in. We developed an archetype‐network framework combining hierarchical clustering, interaction network analysis and catastrophe theory to quantify SES transformations. Analysing 20 indicators across 134 counties in 2000 and 2020, we identified distinct SES archetypes, mapped transition hotspots and assessed inherent sustainability via structural reconfigurations of social‐ecological linkages. This approach captures the nonlinear interactions within SES. Findings indicate five SES archetypes emerging by 2020 that represent a diversification from three types in 2000, with 80 counties shifting archetypes. Key transitions occurred at mountain–plain interfaces: 42.67% of the 2020 agriculture archetype (SES 02) shifted to SES 01 (urban archetype), SES 03 (green development‐archetype) or SES 04 (ethno‐regional fragmented synergy archetype), while 39.58% of nature archetypes transitioned to the enhanced nature archetype (SES 05). Network analysis revealed the dominance of socio‐economic factors. Urban systems (SES 01) showed severe decoupling (network density = 0.14) and the lowest sustainability (0.579), whereas enhanced natural archetypes (SES 05) scored highest (0.787). Sustainability was closely associated with network density (R2 = 0.62), indicating that archetypes with tighter linkages tended to be more resilient. Sustainability transitions in the Songhua River Basin require tailored, context‐specific strategies. Urban areas need innovation‐driven recoupling policies while agricultural regions should adopt circular farming practices to reduce ecological risks. In nature‐dominated areas, ecological restoration must be coupled with sustainable economic opportunities that balance conservation and development, while in ethnically diverse regions, cultural preservation should be combined with environment‐focussed governance for sustainable land management. These findings underscore the need for spatially differentiated, policy‐driven solutions to address the complex SES transformation challenges in the Anthropocene. Read the free Plain Language Summary for this article on the Journal blog.